2016
DOI: 10.1007/s12022-016-9442-7
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metastases of Neuroendocrine Tumors Rarely Show Overlapping Immunoprofile with Hepatocellular Carcinomas

Abstract: The distinction of hepatocellular carcinoma (HCC), neuroendocrine tumor (NET) metastatic to the liver, and cholangiocarcinoma (CC) can sometimes be challenging on small biopsies. Tissue microarrays were constructed from HCCs, NETs, and CCs. The immunoprofile was evaluated using HepPar1, glypican-3 (GPC3), synaptophysin (SYN), chromogranin A (CHR), CD56, MOC-31, and pCEA. One hundred thirteen HCCs, 48 NETs, and 44 CCs were included. Of HCCs, 107 (95 %) expressed HepPar1 and/or GPC3, 52 (46 %) both, and 97 (88 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Increasing evidence suggests soluble GPC3 as a novel diagnostic candidate marker in hepatocellular carcinoma [ 13 ]. GPC3 is expressed in 95% of hepatocellular carcinomas, but not in neuroendocrine tumor metastatic to the liver, and cholangiocarcinoma, measured by liver cancer tissue microarrays which were constructed from hepatocellular carcinoma, neuroendocrine tumor, and cholangiocarcinoma samples [ 23 ]. The high positive rate of GPC3 in hepatocellular carcinoma indicates the specificity of GPC3 in hepatocyte-origin carcinogenesis.…”
Section: Roles Of Gpc3 In Diseasesmentioning
confidence: 99%
“…Increasing evidence suggests soluble GPC3 as a novel diagnostic candidate marker in hepatocellular carcinoma [ 13 ]. GPC3 is expressed in 95% of hepatocellular carcinomas, but not in neuroendocrine tumor metastatic to the liver, and cholangiocarcinoma, measured by liver cancer tissue microarrays which were constructed from hepatocellular carcinoma, neuroendocrine tumor, and cholangiocarcinoma samples [ 23 ]. The high positive rate of GPC3 in hepatocellular carcinoma indicates the specificity of GPC3 in hepatocyte-origin carcinogenesis.…”
Section: Roles Of Gpc3 In Diseasesmentioning
confidence: 99%
“…Though the expression pattern of CD34 (not shown) mimicked the hepatocellular carcinoma, the lack reactivity of hepar1, Glypican-3, AFP and CD10 while high expression of CK7 and CK19 ruled out the diagnosis of hepatocellular carcinoma [10] and supported the diagnosis of ICCA. The neuroendocrine markers, including CgA, Syn and CD56 were negative that excluded the possibility of neuroendocrine tumor/carcinoma [11][12][13]. Likewise, negative expression of germ cell marker (Sall4) also excluded the diagnosis of germ cell tumor.…”
Section: Discussionmentioning
confidence: 99%
“…SYN is considered as the most sensitive biomarker, whereas CgA is the most specific for NETs (21,22). In addition, the percentage of Ki-67 staining is often used as a proliferation marker (23,24). Test yields were calculated for each of the immunohistology markers detected; the results revealed that, on average, SYN had the highest yield (67.0%), followed by CgA (54.8%) and CD56 (19.1%).…”
Section: Discussionmentioning
confidence: 99%